2021
DOI: 10.1007/s00426-021-01585-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of obsessive–compulsive symptomology: mind wandering about the past and future

Abstract: Purpose Obsessive and compulsive tendencies are known to occur in the general population and involve worry around specific concerns (obsessions) and an urge to resolve the concern with thoughts or behaviours (compulsions). Spontaneous, but not deliberate, mind wandering experiences (when attention turns to internal mentation), have been found to predict obsessive– compulsive tendencies [Seli, P., Risko, E.F., Purdon, C. & Smilek, D. (2017). Intrusive thoughts: linking spontaneous mind wandering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 75 publications
(203 reference statements)
0
8
0
Order By: Relevance
“…Obsessive-compulsive tendencies have been found to be associated with experiences of mind wandering (MW) [43]. This connection is explained by the conceptual overlap between these constructs: MW involves a shift of attention towards inner cognitions rather than the external world, which can encompass memories, daydreams, semantic knowledge, and future thoughts.…”
Section: Relationship Between Mind Wandering and Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“…Obsessive-compulsive tendencies have been found to be associated with experiences of mind wandering (MW) [43]. This connection is explained by the conceptual overlap between these constructs: MW involves a shift of attention towards inner cognitions rather than the external world, which can encompass memories, daydreams, semantic knowledge, and future thoughts.…”
Section: Relationship Between Mind Wandering and Ocdmentioning
confidence: 99%
“…These obsessions are characterized by repetitive, persistent, and unwanted thoughts, such as concerns about contamination, which often lead to signif-icant distress and anxiety. Second, compulsions manifest as behaviors or thoughts aimed at alleviating the problem or anxiety [43]. Cognitive models of OCD typically emphasize how ordinary thoughts can evolve into psychopathological obsessions and mental distress.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted a potential link between CDS and mind-wandering and that SCT may represent one characterized by internal distractibility (Becker & Barkley, 2021; Fredrick et al, 2020), and found that CDS symptoms are more significantly linked to greater mind-wandering (Fredrick et al, 2020). Similarly, mind-wandering is also closely related to OCD symptomology, and the intrusive nature of obsessional-compulsive thoughts overlaps with the concept of spontaneous mind-wandering that abruptly into one’s consciousness without any identifiable evoking stimuli (Cole & Tubbs, 2022; Seli et al, 2017). However, according to Christoff and colleagues, mind wandering is a specific state of spontaneous thought that is less constrained and more goal-directed thought compared with rumination and obsessive thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mind wandering can be readily distinguished from rumination and other types of thought that are characterized by the strongest levels of automatic constraints, such as obsessive thought (Christoff et al, 2016). Researchers have found that the type and extent of OCD symptoms are predicted by the frequency of spontaneous, but not deliberate, mind-wandering experiences (Cole & Tubbs, 2022; Seli et al, 2017). It has been revealed that mind-wandering confers an increase in obsessive-compulsive thoughts and the severity of obsessive-compulsive symptoms is positively associated with excessive mind-wandering (Seli et al, 2017; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…MTT research has expanded into clinical populations such as those with depression, anxiety disorders and OCD (Cole & Tubbs, 2022; Gamble et al, 2019; Wu et al, 2015). For example, individuals with Generalised Anxiety Disorder both struggle to imagine positive future events and rate imagined negative events as more likely to occur (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%